Associations between ideal blood pressure based on different BMI categories and stroke incidence. Issue 7 (July 2020) - Zheng, Liqiang; Xie, Yanxia; Zheng, Jia; Guo, Rongrong; Wang, Yali; Dai, Yue; Sun, Zhaoqing; Xing, Liying; Zhang, Xingang; Sun, Yingxian
Abstract : Objectives: The 2017 American College of Cardiology/American Heart Association (ACC/AHA) Guideline for high blood pressure (BP) in adults redefined hypertension as SBP at least 130 mmHg or DBP at least 80 mmHg. However, the optimal BP for different BMI population to reduce stroke incidence is uncertain. Methods: A prospective cohort study was designed by four examinations: baseline (2004–2006), 2008, 2010 and 2017 follow-up. The study group composed of 36 352 individuals, to determine the ideal BP range to reduce stroke incidence of two BMI level, adjusted Cox proportional hazards models were utilized to establish the associations between SBP/DBP and the risk of stroke incident. Then, the restricted cubic spline regression was applied to find the ideal range of SBP/DBP values for two kinds of BMI categories definitions. Results: During a median follow-up period of 12.5 years, 2548 (7.0%) nonstroke individuals at baseline developed incident stroke. After fully adjusting confounding factors, SBP (per 20 mmHg increase) and DBP (per 10 mmHg increase) are independently associated with the risk of stroke incidence [SBP, hazard ratio = 1.277, 95% confidence interval (95% CI), 1.217–1.340, P  < 0.001; DBP, hazard ratio = 1.138, 95% CI, 1.090–1.189, P  < 0.001]. Conclusion: Our study revealed that the ideal BP for a population with BMI less than 24 kg/m 2 was less than 130/80 mmHg, whereas the ideal BP for BMI at least 24 kg/m 2 was less than 120/80 mmHg. The sensitivity analyses between BMI less than 25 kg/m 2 and BMI at least 25 kg/m 2 showed similar findings. This finding provides more accurate primary prevention strategies based on various BMI populations.